IVIG activates FcγRIIB-SHIP1-PIP3 Pathway to stabilize mast cells and suppress inflammation after ICH in mice. Issue 1 (December 2017) - Akyol, Gokce; Manaenko, Anatol; Akyol, Onat; Solaroglu, Ihsan; Ho, Wing; Ding, Yan; Flores, Jerry; Zhang, John; Tang, Jiping
Abstract Following intracerebral hemorrhage (ICH), the activation of mast cell contributes to brain inflammation and brain injury. The mast cell activation is negatively regulated by an inhibitory IgG-receptor. It's signals are mediated by SHIP (Src homology 2-containing inositol 5′ phosphatase), in particular SHIP1, which activation leads to hydrolyzation of PIP3 (Phosphatidylinositol (3, 4, 5)-trisphosphate (PtdIns(3, 4, 5)P3, leading to the inhibition of calcium mobilization and to the attenuation of mast cell activation. Intravenous immunoglobulin (IVIG) is a FDA-approved drug containing IgG. We hypothesized that IVIG will attenuate the ICH-induced mast cell activation via FcγRIIB/SHIP1 pathway, resulting in a decrease of brain inflammation, protection of the blood-brain-barrier, and improvement of neurological functions after ICH. To prove this hypothesis we employed the ICH collagenase mouse model. We demonstrated that while ICH induced mast cell activation/degranulation, IVIG attenuated post-ICH mast cell activation. Mast cell deactivation resulted in reduced inflammation, consequently attenuating brain edema and improving of neurological functions after ICH. Furthermore using siRNA-inducedin vivo knockdown approach we demonstrated that beneficial effects of IVIG were mediated, at least partly, via SHIP1/PIP3 pathway. We conclude that IVIG treatment represents a promising therapeutic approach potentially able to decrease mortality and morbidity after ICH in experimental models.